The Reorientation of Indonesia’s Maritime Fulcrum in Addressing Shifting Priorities and Strategic Challenges - Munabari, Fahlesa; Sellita (Lembaga Ketahanan Nasional Republik Indonesia, 2024)
Purpose: The aim of this article is to review the literature related to Indonesia’s Global Maritime Fulcrum (GMF) policy, which was initiated by President Joko Widodo at the beginning of his administration in 2014. This study seeks to identify the challenges that arose during the transition and implementation of the GMF policy, particularly in the period from 2014 to 2019. Study Design/Methodology/Approach: This article employs a qualitative research method with a descriptive-analytical approach. Literature sources such as journal articles, opinion pieces, books, and documents from relevant ministries and agencies are utilized to analyze the trends in the development of PMD policy during the second half of President Joko Widodo's administration. Findings: The findings indicate that most recent literature suggests a shift in priorities during President Joko Widodo's second term (2014-2019) concerning the GMF policy. This shift is evident from the decreasing focus on GMF in various speeches and governmental policies, alongside a greater emphasis on land-based infrastructure and economic development rather than maritime. The article categorizes the factors contributing to this shift into two major groups: external challenges and internal challenges. The primary external challenge currently faced by Indonesia is the increasing aggressiveness of China in the South China Sea. Meanwhile, the internal challenges include the limitations of military budgets, the COVID-19 pandemic, the allure of China's economic incentives, and a lack of coordination among related ministries and agencies.Top of FormBottom of Form Originality/Value: The study underscores the need on GMF issues should focus more on the prioritization of GMF programs. Additionally, relevant ministries and agencies need to establish realistic priorities within the GMF program, considering current budgetary constraints and the socio-political and economic landscape, to effectively achieve the GMF vision.